Development of microbiological diffusion inhibition test for the determination of antibiotic residues in the milk - Aktayeva, S.; Sarsen, A.; Mussakhmetov, A.; Kiribayeva, A.; Tursunbekova, A.; Khassenov , B. (Eurasian Journal of Applied Biotechnology, 2023)
Antimicrobial agents are used in animal husbandry for the prevention and treatment of diseases in farm animals and have become an indispensable aspect of commercial livestock production. Antimicrobial therapy is well-established as a component of comprehensive preventive measures aimed at minimizing diseases in farm animals and has been incorporated into procedures directed at promoting livestock growth and productivity. Bacillus licheniformis strain T7 is susceptible to the antibiotics clidamycin, rifampicin, erythromycin, ciprofloxacin, tobramycin, tetracycline, penicillin, streptomycin, and chloramphenicol, has good sporogenic properties, grows rapidly on nutrient agar at 30-55 °C, pH 5.5–8.0, and can serve as a test culture in a microbial inhibitor test. Bacillus licheniformis T7 spores were obtained by growing the culture in Difco sporulation medium and then inactivating the vegetative cells at 90 °C for 20 minutes. Endospores of Bacillus licheniformis T7 co-polymerized with nutrient agar and germinated at 55 °C for 3–3.5 h, resulting in a pH shift from 5.5 to >6.5, which can be measured with an acid-base indicator. Bromocresol purple was suggested as a pH indicator for use in a microbiological inhibition test, wherein the presence of antibiotics or other compounds impeding the development of a microbiological culture could be determined by a change in the agar’s color. A microtube- and plate-based microbiological inhibitor test prototype has been developed.